2018
DOI: 10.1007/s00423-018-1658-1
|View full text |Cite
|
Sign up to set email alerts
|

Modified ante situm liver resection without use of cold perfusion nor veno-venous bypass for treatment of hepatic lesions infiltrating the hepatocaval confluence

Abstract: Ante situm liver resection can be applied without cold perfusion nor veno-venous bypass with acceptable morbidity and mortality. However, this procedure remains challenging even for the experienced hepato-pancreato-biliary surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Preoperative evaluation of patients who are candidates for this surgical technique is important, as this technique should only be considered for patients who have a normal liver function with non-resectable tumors [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative evaluation of patients who are candidates for this surgical technique is important, as this technique should only be considered for patients who have a normal liver function with non-resectable tumors [4].…”
Section: Discussionmentioning
confidence: 99%
“…In this technique, first, the liver is resected, after which ex situ surgery is performed on the part of the liver which includes the tumor. Finally the part of the liver segments which do not include the tumor are re-transplanted [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…One article was omitted due to duplicate data [33]. This resulted in 14 articles included in the final qualitative synthesis [14,[34][35][36][37][38][39][40][41][42][43][44][45][46]. All 14 articles were case series and thus uncontrolled-observational trials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unfortunately, these procedures are limited by hepatic intolerance to warm ischemia, hemodynamic instability, and intestinal vasculature congestion [49]. In an attempt to ameliorate these complications, venovenous bypass and hypothermic hepatic perfusion are commonlyusedstrategies [31,43,50]. Of the surveyed reports in this review, 20% of cases utilized an ex vivo approach; whereas only 3% performed an ante situm resection and 10% an in situ approach.…”
Section: Study Population and Surgical Characteristicsmentioning
confidence: 99%
“…They showed that the ante situm liver resection can be safely performed in an experienced HPB center without hypothermia and veno-venous bypass [1]. However, we have some questions and comments:…”
mentioning
confidence: 95%